1998
DOI: 10.1046/j.1365-2222.1998.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II DRB1, DQB1 and DPB1 genotypic associations with peanut allergy: evidence from a family‐based and case‐control study

Abstract: While other genetic factors may be important, results from this study indicate that HLA class II genetic polymorphism may play a role in determining susceptibility to peanut allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 34 publications
3
65
1
3
Order By: Relevance
“…[5][6][7] An association has been previously demonstrated between DQB1 allele and PA by Howell et al 7 The present results do not replicate the increase of the DQB1*04 allele in PA cases as previously published; 7 however, we showed an increase of the DQB1*06:03P allele and a decrease of the DQB1*02, DQB1*03:02P, DQB1*05 and DQB1*05:01P alleles in PA subjects compared with controls. The association of the DQB1*06:03P and DQB1*02 alleles with PA remained significant after adjusting for asthma status and sex.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…[5][6][7] An association has been previously demonstrated between DQB1 allele and PA by Howell et al 7 The present results do not replicate the increase of the DQB1*04 allele in PA cases as previously published; 7 however, we showed an increase of the DQB1*06:03P allele and a decrease of the DQB1*02, DQB1*03:02P, DQB1*05 and DQB1*05:01P alleles in PA subjects compared with controls. The association of the DQB1*06:03P and DQB1*02 alleles with PA remained significant after adjusting for asthma status and sex.…”
Section: Discussioncontrasting
confidence: 51%
“…3 Genes of the HLA family, which are part of the major histocompatibility complex (MHC) locus, are involved in antigen presentation to T cells. As asthma and food allergy are known to be clinically correlated, 4 a few studies have examined MHC class II genes (HLA-DR, -DQ and -DP families) in the context of PA [5][6][7] but only one study has shown a link between these genes and hypersensitivity to peanut. 7 To better understand the genetic component of PA, we compared the HLA-DQB1 allele and genotype frequencies in children with PA and children without PA and demonstrated an association between the HLA-DQB1 gene and this disease.…”
Section: Introductionmentioning
confidence: 99%
“…6,23 Previous studies have provided evidence for association between susceptibility to allergy (with or without asthma-related symptoms), and HLA-DR4 and/or the DR7 allele. 24 Howell et al 25 have also demonstrated significant increase in HLA-DRB1*08, and the DQB1*04 allele in peanut allergy patients.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding a food allergy diagnosis, although children were not food challenged, the definition of food allergy for this study was more stringent than most published large-scale epidemiologic studies of food allergy. [23][24][25][26][27] A unique strength of this study was that families of children with food allergy were enrolled along with their siblings, who may or may not had allergic diagnoses. The subjects and controls were of similar genetic makeup and were raised similarly.…”
Section: Discussionmentioning
confidence: 99%